Quantum teaching based on augmented reality to elevate critical thinking and metacognition of senior high school students in Indonesia - Siswati, Bea Hana; Pitaloka , Firda Ayu; Wahono, Bevo (Journal on Biology and Instruction, 2025)
This study investigates the effect of the Augmented Reality (AR)-based Quantum Teaching model on high school students’ critical thinking and metacognitive skills in biology. The need for innovative learning models is urgent to enhance students’ higher-order thinking abilities, which are crucial for meeting the demands of 21st-century learning. This research employed a quasi-experimental pre-test post-test control group design involving grade XI biology students at Pakusari State High School during the 2023/2024 academic year. Random sampling assigned class XI 5 as the experimental group and XI 4 as the control group. Data collection methods included observations, interviews, essay tests, and documentation. Data analysis using ANCOVA via SPSS version 26 revealed significant improvements in both critical thinking and metacognitive skills in the experimental group compared to the control group. These findings demonstrate that the AR-based Quantum Teaching model effectively enhances students’ cognitive and selfregulatory skills in biology learning. The study concludes that integrating AR technology within innovative teaching models can foster critical competencies essential for students’ academic success and lifelong learning. The implications of this research suggest that schools and educators should consider adopting AR-supported pedagogies to enrich the learning experience and promote deeper understanding. Educational stakeholders are encouraged to invest in teacher training and digital infrastructure to support the successful implementation of such models. Furthermore, this study provides a foundation for developing curriculum innovations that combine interactive technology and student-centered approaches, aiming to prepare learners with the critical and metacognitive skills necessary for future academic and professional challenges.